Evidence of crustal growth during the Svecofennian orogeny: New isotopic data from the central parts of the Paleoproterozoic Central Finland Granitoid Complex - Heilimo Esa; Mikkola Perttu; Ahven Marjaana; Huhma Hannu; Lahaye Yann; Virtanen Ville J. (Elsevier B.V., 2025)
The Central Finland Granitoid Complex (CFGC) is the Paleoproterozoic core of the Svecofennian orogeny composed mainly of plutonic rocks varying from diorites to granodiorites and granites. Common mixing and mingling textures, synplutonic dykes, and mafic magmatic enclaves highlight the simultaneous nature of mafic, mantle derived magmatism and more evolved felsic magmatism in the CFGC. New U-Pb geochronological data support crustal growth during 1.90–1.87 Ga for the CFGC. Both Sm-Nd (εNd -1.7–+2.5) from whole rocks and Lu-Hf (εHf -8–+9) from zircons point towards relatively juvenile sources for the plutonic rocks without Archean crustal component. On the whole, isotopic evidence collectively points to crustal growth with maturing arc characteristics at 1.90–1.87 Ga, and a possible amalgamation of island arcs during the Svecofennian orogeny. In a larger scale, the CFGC was 1.9 Ga ago located in the active margin of the Great Proterozoic Accretionary Orogen when supercontinent Columbia (Nuna) formed.